2019
DOI: 10.1111/ijac.13386
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behavior studies of chemically bonded phosphate ceramic coatings reinforced with modified multi‐walled carbon nanotubes (MWCNTs)

Abstract: To improve the wear resistance of the chemically bonded phosphate ceramic coatings, MWCNTs are selected as the reinforcement after the modification. The high temperature wear experiment is carried out to investigate the wear behavior of the coatings with different temperatures. The results suggest that, when the temperature is below 500℃, MWCNTs can decrease friction coefficient, and the lowest friction coefficient is about 0.28, but MWCNTs lose the lubricant function at 500℃ and the friction coefficient keeps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…28,29 Recent studies have shown that consuming LAB, such as bidobacteria, can alleviate lipopolysaccharide and D-galactoseinduced acute liver injury. 30,31 Another study showed that combining Lactobacillus plantarum and L-arginine can protect against endotoxin-induced liver damage. 32 CCl 4 -induced liver injury can cause signicant intrahepatic inammation and liver brosis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Recent studies have shown that consuming LAB, such as bidobacteria, can alleviate lipopolysaccharide and D-galactoseinduced acute liver injury. 30,31 Another study showed that combining Lactobacillus plantarum and L-arginine can protect against endotoxin-induced liver damage. 32 CCl 4 -induced liver injury can cause signicant intrahepatic inammation and liver brosis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, tribochemical reactions induced by functional fillers and the counterface are also conducive to the promotion of the wear resistance of composite coatings. 1,2,7−25 As a kind of layered silicate mineral, the main component of natural serpentine is magnesium silicate hydroxide, Mg 3 Si 2 O 5 (OH) 4 , in which silicon-oxygen tetrahedron and magnesia-oxygen (oxyhydrogen) octahedron constitute the basic structural unit (TO layer), and each of them is held together through hydrogen bond and Van der Waals force. The hightemperature stability of natural serpentine is excellent and its layered structure is well maintained even at 600 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate bonded solid coatings possess superior temperature resistance property. But high brittleness and inferior anti-wear performance of the phosphate binder greatly impede its practical application [8][9][10][11][12][13]. Studies reveled that with appropriate incorporation of functional llers can effectively promote anti-wear performance of the composite coatings [4][5][6][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies reveled that with appropriate incorporation of functional llers can effectively promote anti-wear performance of the composite coatings [4][5][6][14][15][16][17][18][19][20][21][22][23][24]. Additionally, because process high fracture toughness, brous functional llers can be selected to reduce the brittleness of the composite coatings [11,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%